Association between single nucleotide polymorphisms in exon 3 of the alpha-A-crystallin gene and susceptibility to age-related cataract. (4th March 2023) - Zhao, Zhennan; Chen, Jiahui; Yuan, Wenyi; Jiang, Yongxiang; Lu, Yi
ABSTRACT: Background: The mutations in the αA-crystallin (CRYAA) gene may contribute to the development of age-related cataract (ARC). In this study, we searched for single nucleotide polymorphisms (SNP) in exons of CRYAA and investigated the associations between the identified SNPs and the subtypes of ARC. Materials and methods: Peripheral venous blood was collected for the extraction of genomic DNA. Three exons of CRYAA were sequenced to detect SNPs. The frequency distributions of alleles and genotypes were compared between the ARC and control groups. Results: There were 618 patients with various subtypes of ARC (nuclear cataract [NC], cortical cataract [CC], posterior subcapsular cataract [PSC]). The control group comprised 236 patients. The incidence of early-onset cataract was significantly greater in PSC patients ( P  = .002 for NC; P  = .036 for CC). One SNP was detected in exon 3 of CRYAA (rs76740365 G>A). When the distribution of rs76740365 was compared among the ARC subtypes, only the difference between the PSC group and the control group was statistically significant (allele frequency: P  = .000057, OR 2.945; genotype distribution frequency: P  = .000458). The heterozygote genotype (GA) carried a significantly greater risk than the homozygous wild-type genotype (GG) by 1.742 times for all types of cataracts and 2.369 times for the PSC subtype. Conclusions: The SNP rs76740365 G>A in exon 3 of the CRYAA gene is associated with greater susceptibility of ARC, particularly the PSC subtype. Individuals carrying the SNP rs76740365 G>A may be more likely to develop PSC at a younger age than other subtypes.